Relationship Between Climate Class and The Learning Outcomes of Light Vehicle Engineering Training Participants in The Padang Jobs Training House - Zikria Wahyuni; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low learning outcomes of the light vehicle engineering training participants which was thought to be caused by the less conducive climate for the light vehicle engineering training participants' class at the Padang Vocational Training Center. This study aims to see an overview of the class climate of the training participants, to see an overview of the learning outcomes of the training participants, and to see the relationship between the Class Climate and the Learning Outcomes of the Light Vehicle Engineering Training Participants at the Padang Job Training Center.This research is a correlational study that uses a quantitative approach. The population in this study were participants in the light vehicle engineering training class 2020. The data collection technique used was a questionnaire and the tools used were a written list of questions. The data analysis technique used the percentage formula and the Spearman Rho formula.The results of this study indicate that: (1) The climate of the training participants' class was categorized as very unfavorable; (2) The learning outcomes of the light vehicle engineering training participants are categorized as low; (3) There is a significant relationship between the classroom climate and the learning outcomes of participants in light vehicle engineering training at the Padang Vocational Training Center. The suggestion of this research is that it is hoped that the instructor will improve the classroom climate in light vehicle engineering training. Institution managers should facilitate instructors to create a classroom climate Keywords: Classroom Climate, Learning Outcomes